The Thermal Insulation Of Mine Airways - Bottomley, Paul (My University, 2015)
The application of insulation material to the surfaces of airways has the potential of reducing the heat load on the ventilation air of deep mi ne s. This study aims at assessing the viability of this technique. Previous investigations on heat transfer from insulated airways are reviewed and are found to be flawed or out of date. A more reliable thermal analysis is presented This shows that reductions in heat load of 50 to 70 percent can be achieved in fully insulated tunnels, 20 to 40 per cent with partial insulation (footwall uninsulated) and less than 20 per cent with the footwall both uninsulated and Net. Nomograms are presented which predict the reduction in heat load for a wide range of conditions An experimental study on tunnel insulation in a deep gold mine is reported The reductions in heat load were 57 per cent with full insulation, and 30 per cent with partial insulation. These values are lower than those predicted, namely 71 and 50 per cent respectively, largely because of the uneven thickness of the insulation layer Guidelines are provided for the selection of insulation systems. Estimates of the financial benefits accruing from the insulation of airways are presented.